2020
DOI: 10.1051/sicotj/2020003
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic surgical drainage is associated with increased infection following intramedullary nailing of diaphyseal long bone fractures: A prospective cohort study in Nigeria

Abstract: Introduction: Prophylactic surgical drains are commonly used in Nigeria following intramedullary nailing (IMN) of long bone diaphyseal fractures. However, evidence in the literature suggests that drains do not confer any benefit and predispose clean wounds to infection. This study compares outcomes between patients treated with and without prophylactic surgical drainage following diaphyseal long bone fractures treated with IMN. Methods: A prospective cohort study with randomization was conducted at a tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…9 Use of a closed suction drain in the postoperative period is another common tool used in many orthopaedic surgeries. 2,[10][11][12] The underlying concept of using it is to prevent haematoma formation, thereby promoting uneventful wound healing. It has been suggested that a positive drain tip culture may help in predicting SSI while a negative culture would virtually exclude the possibility of SSI.…”
Section: Introductionmentioning
confidence: 99%
“…9 Use of a closed suction drain in the postoperative period is another common tool used in many orthopaedic surgeries. 2,[10][11][12] The underlying concept of using it is to prevent haematoma formation, thereby promoting uneventful wound healing. It has been suggested that a positive drain tip culture may help in predicting SSI while a negative culture would virtually exclude the possibility of SSI.…”
Section: Introductionmentioning
confidence: 99%